Termin zawity do zaskarżania uchwał właścicieli lokali - Grela, Jacek (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2024)
The issue of appealing against resolutions of owners of separate premises has already received numerous opinions from both jurisprudence and legal scholars. Discussed, among others: the active and passive locus standi of the parties in the process in which a given resolution was challenged, attention was paid to the legal nature of the request in which the resolution was challenged, and finally, the nature of the sanction for the defectiveness of the legal act was indicated. However, as it turns out, not all issues were discussed, and certainly not all emerging doubts were resolved. An example of an institution causing divergences of views both in legal science and jurisprudence is the essence of the deadline for appealing against a resolution. This article attempts to solve the difficulties that arise in this area.
Keywords: prawo rzeczowe; własność lokali; uchwały właścicieli; zaskarżanie uchwał; terminy zawite